FAKTOR PENYEBAB BELUM DIDAFTARKANNYA ALOE VERA PONTIANAK SEBAGAI INDIKASI GEOGRAFIS - NIM. A1011141108, IDA PADHILLAH (Jurnal Fatwa Hukum, 2024)
AbstractAloe Vera is an agricultural product cultivated in West Kalimantan, particularly in the city of Pontianak. Aloe Vera from Pontianak has distinctive characteristics compared to Aloe Vera from other regions outside of West Kalimantan. Its superiority lies in the large size of its leaves, high water content, and thick flesh. Products protected by Geographical Indications (GI) are those that possess specific characteristics and qualities not found in similar products, such as Aloe Vera from Pontianak. However, to date, no efforts have been made to protect Aloe Vera as a Geographical Indication, despite its potential value as one This thesis aims to identify the factors contributing to the lack of registration of Aloe Vera as a Geographical Indication. The method used to obtain data in this research involves literature review to gather secondary data and field studies conducted through observation and interviews with informants.The results of this study indicate that Aloe Vera from Pontianak is a valuable product with the potential for Geographical Indication protection due to its distinct characteristics compared to Aloe Vera from other regions. Based on substantive requirements, Aloe Vera meets the criteria outlined in Articles 1, 3, and 6 paragraph (3) of Government Regulation No. 51 of 2007 concerning Geographical Indications. The factors contributing to the lack of registration of Aloe Vera as a Geographical Indication are primarily financial. This includes the costs associated with research necessary for compiling the requirements for Geographical Indication registration and efforts to educate the Geographical Indication Rights Holders (MPIG) through seminars. Ultimately, relevant authorities have been passive in pursuing the registration of Aloe Vera from Pontianak as a Geographical Indication due to concerns over the high expenses involved.Keyword: Registration, Geographical indication, Aloe VeraAbstrakAloe Vera adalah produk pertanian yang dibudidayakan di Kalimantan Barat khususnya dikota Pontianak. Aloe Vera Pontianak mempunyai ciri khas yang berbeda dengan Aloe Vera di daerah lain (di luar Kalimantan Barat). Keunggulannya adalah ukuran Pelepah yang besar dan memiliki kandungan air yang banyak serta daging buah yang tebal. Produk yang dilindungi Indikasi Geografis adalah produk yang memiliki ciri dan kualitas tertentu yang tidak dimilki oleh produk sejenis lainnya seperti halnya Aloe Vera Pontianak. Namun sampai saat ini belum ada yang mengupayakan perlindungan Indikasi Geografis terhadap Aloe Vera padahal produk ini bernilai Indikasi Geografis atau berpotensi mendapatkan perlindungan Indikasi Geografis. Skripsi ini bertujuan untuk mengetahui faktor penyebab belum didaftarkannya Aloe Vera sebagai Indikasi Geografis. Metode yang digunakan untuk memperoleh data dalam penelitian ini adalah dengan cara studi pustaka untuk memperoleh data sekunder dan studi lapangan dengan melakukan observasi serta wawancara dengan informan. Adapun hasil penelitian ini menunjukan bahwa produk Aloe Vera Pontianak merupakan produk yang bernilai dan berpotensi untuk mendapatkan perlindungsan Indikasi Geografis karena memiliki karakteristik yang berbeda dengan Aloe Vera didaerah lain. Berdasarkan syarat substantive, produk Aloe vera memenuhi syarat yang tertera pada pasal 1 angka 1, pasal 3 dan pasal 6 ayat (3) yang diatur dalam PP No. 51 2007 tentang Indikasi Geografis. Faktor penyebab belum didaftarkannya Aloe Vera sebagai indikasi geografis disebabkan oleh faktor finansial, yakni untuk keperluan riset yang hasilnya akan dituangkan di buku persyaratan Indikasi Geografis, untuk upaya pemahaman Masyarakat Pemilik Indikasi Geografis (MPIG) terkait Indikasi Geografis melalui seminar-seminar, pada akhirnya berakibat dinas terkait menjadi   pasif dalam mengupayakan pendaftaran Indikasi Geografis Aloe Vera Pontianak dikarenakan mengkhawatirkan biaya yang mahal  Kata Kunci: Pendaftaran, Indikasi Geografis, Aloe Vera